Visible Light Absorption Characteristics of M-Nitrogen (M= Mn, Fe, Co, Ni, Cu) Co-Doped Monodisperse TiO2 Microparticles. Issue 1806 (2015) - Mathis, John E.
ABSTRACT: There is great interest in improving TiO2 's photocatalytic activity in the visible portion of electromagnetic spectrum. Recent work has shown that co-doping mesoporous TiO2 microparticles with a transition metal and nitrogen, hereby designated as (M, N) TiO2, significantly increases its visible light absorption. However, the hydrothermal method used to produce the microparticles creates a wide distribution in the size of the microparticles, which could affect the absorption properties. Recently, it has become possible to produce monodisperse, mesoporous TiO2 microparticles with engineered sizes using a hybrid sol-gel/hydrothermal technique. Further, it has also been shown that the size of monodisperse TiO2 microparticles affects the the photocatalytic activity. This study investigated whether using mondodisperse (M, N) TiO2 microparticles would further increase visible-light absorption for (M, N)TiO2 . The first-row transition metals chosen for this study - Mn, Fe, Co, Ni, and Cu – have been characterized in the earlier (M, N) TiO2 UV-vis study, which was used as a baseline. The doping levels of the transition metals samples were set at the 2.5 percent level previously shown to be optimum for photocatalytic activity.